2018
DOI: 10.5430/jnep.v8n6p85
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy treatment: Colorectal cancer patients’ perception

Abstract: Background and objective: The chemotherapy cause greater impact in the physical and emotional sphere and in the experience of the symptoms. Thus, knowing the perception of these patients, is necessary to obtain subsidies that may direct the implementation of effective interventions for the management of adverse events and the support offering regarding the experience of the disease and treatment, with better impact on the quality of life. The objective of this study was to explore the perception of colorectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Knowing the most appropriate protocol for treating a type of cancer does not mean implicitly and cope with the emotional and disease adaptation problems of patients; the model of the disease that includes the clinical, paraclinical, certainty diagnosis, of the suffering, which refers to the perception of the condition of the patient(13,18).This study showed a lower-thanexpected level of understanding of cancer treatment; allocating a longer time to each future.Because previous research has not focused on understanding the perception of cancer patients in Romania on an oncological specific treatment, we could consider this study a first step in trying to explore new ways in order to improve the quality of medical care. Considering the complexity of the cancer patient's care goals, his and his family's expectations, the varied range of therapeutic options, effective communication becomes a critical element in the role of the oncologist, especially in the case of incurable patients.Communication is a challenge that requires patience, improving interpersonal and counseling skills in order to facilitate effectiveness and choice of options in a properly informed environment.…”
mentioning
confidence: 83%
“…Knowing the most appropriate protocol for treating a type of cancer does not mean implicitly and cope with the emotional and disease adaptation problems of patients; the model of the disease that includes the clinical, paraclinical, certainty diagnosis, of the suffering, which refers to the perception of the condition of the patient(13,18).This study showed a lower-thanexpected level of understanding of cancer treatment; allocating a longer time to each future.Because previous research has not focused on understanding the perception of cancer patients in Romania on an oncological specific treatment, we could consider this study a first step in trying to explore new ways in order to improve the quality of medical care. Considering the complexity of the cancer patient's care goals, his and his family's expectations, the varied range of therapeutic options, effective communication becomes a critical element in the role of the oncologist, especially in the case of incurable patients.Communication is a challenge that requires patience, improving interpersonal and counseling skills in order to facilitate effectiveness and choice of options in a properly informed environment.…”
mentioning
confidence: 83%
“…4 O impacto negativo da doença e do tratamento oncológico, em virtude de seus efeitos colaterais, perpassa o aspecto físico do indivíduo e alcança outros aspectos, como o psicológico-emocional, o familiar, o social, o laboral, entre outros. 5,6 Ao analisar a literatura, [5][6][7][8] foram identificados alguns panoramas relacionados aos pacientes com câncer, como necessidades nos aspectos físico, estilo de vida diário, psicológico, assistência da saúde, informação, reabilitação, suporte emocional, comunicação, financeiro, espiritual, autonomia, sexualidade e nutrição.…”
Section: Introductionunclassified
“…Different researchers investigated the treatment perceptions of colorectal cancer patients on the daily activity or experience of the adverse symptom [48][49][50] .The perceptions of colorectal cancer survivors were also reported 51 . In 2018, Ticona-Benavente, et al 52 studied the perceptions of colorectal cancer patients during adjuvant chemotherapy. The study revealed that most patient's perceptions were negative experiences.…”
Section: Dietary Perception In Colorectal Cancer Patients During Adju...mentioning
confidence: 99%